Prognostic Significance of Increasing pSOFA Scores in Paediatric Sepsis - Nadia Setianingsih; Yunnie Trisnawati; Arlinda Sari Wahyuni; Bugis Mardina Lubis; Hendri Wijaya; Rosmayanti Syafriani Siregar (Indonesian Journal of Global Health Research, 2026)
Sepsis is a major cause of morbidity and mortality among children worldwide, particularly in low- and middle-income countries. Early identification and continuous monitoring of organ dysfunction are critical components in paediatric sepsis management. The Paediatric Sequential Organ Failure Assessment (pSOFA) score is used to evaluate organ dysfunction and predict the risk of mortality. The aim of the study was to investigate the association between an increase in pSOFA score (∆pSOFA) and mortality among paediatric sepsis patients. This retrospective cohort study included paediatric patients aged 1 month to 18 years diagnosed with sepsis and treated in the PICU from January to December 2023. Receiver Operating Characteristic (ROC) curve analysis was performed to evaluate the predictive value of the pSOFA score for mortality. A total of 87 patients were included in the analysis, with 36 deaths recorded within the first 7 days. Patients with ∆pSOFA ≥1 had a six-fold higher risk of mortality (p<0.001; 95% CI: 3.26–11.02). The day-1 pSOFA score showed poor predictive ability (AUC=0.50), whereas the day-3 score demonstrated good predictive performance (AUC=0.85). An increase in the pSOFA score is significantly associated with a higher risk of mortality in paediatric sepsis patients.